Social engagement and the elderly in rural Indonesia. (May 2019) - Utomo, Ariane; Mcdonald, Peter; Utomo, Iwu; Cahyadi, Nur; Sparrow, Robert
Abstract: Rural areas in Indonesia are older relative to urban areas. This paper questions how levels of social engagement vary across among the elderly in rural Indonesia. A sample of 2750 respondents aged 60 and over was drawn from 10 purposely-selected relatively "old" villages. Our three measures of social engagement are: participation in income-generating activities, in communal activities, and in care work. While there are notable village-level differences in patterns of social engagement, the majority of our respondents are actively engaged in productive activities in their old age until they can no longer be so. A negative educational gradient in the likelihood of work participation suggests that needs for income security is a driver of the elderly's work participation. The notion of promoting active ageing, as typically understood in the Western and/or urban contexts, is of secondary importance to health care provision and managing old-age disability in these ageing rural communities. Highlights: Fertility decline and out-migration created pockets of ageing in rural Indonesia. We analysed how social engagement varies among persons aged 60 + in 10 villages. Living in poorer villages is associated with higher odds of social engagement. Those with lower education have higher odds of working in old age. Policy should focus on health care provision and managing old-age disability.